Nanophotonic crystals on unpolished sapphire substrates for deep-UV light-emitting diodes - Tinh Binh Tran (Nature Portfolio, 2021)
Abstract A new method has been established and employed to create a random nanophotonic crystal (NPhC) structure without photolithography on the unpolished side of a single-side-polished sapphire substrate. This nano structure has potential use in enhancing the light-extraction efficiency (LEE) of deep ultraviolet light-emitting diodes (DUV-LEDs), and has never been built for DUV-LED applications before. Two mask layers in the nano scale (Au and SiO2) were used to create the NPhC and observed using scanning electron microscopy to have an average height of 400 nm and various sizes from 10 to 200 nm. Finally, a conventional DUV-LED and a DUV-LED device with NPhC were simulated using 2D Lumerical Finite-Difference Time-Domain (FDTD) for comparison. The results show that the LEE of the DUV-LED device with this NPhC integrated was significantly directly enhanced by up to 46% and 90% for TE and TM modes, respectively, compared to the conventional DUV-LED device. Thus, this NPhC is believed to be a new, key technique to enhance the LEE of DUV-LEDs.